A Pedestal, A Table, A Love Letter: Archaeologies of Gender in Videogame History - Nooney, Laine (Game Studies, 2013)
The history of videogames has largely been imagined as a patrilineal timeline. Women, when they emerge as participants in the game industry, are typically figured as outliers, exceptions, or early exemplars of “diversity” in the game industry. Yet the common practice of “adding women on” to game history in a gesture of inclusiveness fails to critically inquire into the ways gender is an infrastructure that profoundly affects who has access to what kinds of historical possibilities at a specific moment in time and space. This contribution aims to shift the relevant question from “Where are women in game history?” to “Why are they there in the way that they are?” To do so, the essay strategically deploys Sierra On-Line co-founder and lead designer Roberta Williams as an exceptional case study on the problem of gender in videogame history. Drawing from both media archaeology and feminist cultural studies, this contribution first outlines the function Roberta Williams serves as a gendered subject of game history. The remainder of the essay is organized as three short, non-chronological vignettes about specific objects and practices in the biography of Roberta Williams. Attention to the contextual specificity of Roberta Williams and her historical moment produces an alternative genealogy for gaming centered around relations of intimacy and labor in domestic space. Rather than producing a chronology, the method of this essay illustrates a historical critique by sketching a contour that unsettles the presumptive logic of what we must account for when we write about the objects and subjects of game history.
Number: 2
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé